AKUNTANSI CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA BANK SYARIAH - Ismayanti, Nurul Fitri (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
This journal describes how the Islamic banks reporting and exposing their corporate social responsibility to the community in general and shareholders in particular. As we know, that every company, especially companies tbk., Must set aside part of its profts to social activities, which is better known as Corporate Social resposibility (CSR). CSR is intended to demonstrate corporate responsibility to the communities in which they operate. This CSR activity should be reported by the company to the public and shareholders, in the form of CSR report. However, in practice, there are still some companies that have not been compiled neatly the CSR report. Even in Islamic banks, only a few banks that have issued its CSR report. In this paper, the author will discuss how CSR report should be made, and disclosure.Keywords: Bank Syariah, CSR, Responsibility Accounting